Single-step bioconversion of lignocellulose to hydrogen using novel moderately thermophilic bacteria - Cao, Guang-Li (BioMed Central, 2014)
BACKGROUND: Consolidated bioprocessing (CBP) of lignocellulosic biomass to hydrogen offers great potential for lower cost and higher efficiency compared to processes featuring dedicated cellulase production. Current studies on CBP-based hydrogen production mainly focus on using the thermophilic cellulolytic bacterium Clostridium thermocellum and the extremely thermophilic cellulolytic bacterium Caldicellulosiruptor saccharolyticus. However, no studies have demonstrated that the strains in the genus Thermoanaerobacterium could be used as the sole microorganism to accomplish both cellulose degradation and H(2) generation. RESULTS: We have specifically screened for moderately thermophilic cellulolytic bacteria enabling to produce hydrogen directly from conversion of lignocellulosic materials. Three new strains of thermophilic cellulolytic bacteria in the genus Thermoanaerobacterium growing at a temperature of 60°C were isolated. All of them grew well on various plant polymers including microcrystalline cellulose, filter paper, xylan, glucose, and xylose. In particular, the isolated bacterium, designated as Thermoanaerobacterium thermosaccharolyticum M18, showed high cellulolytic activity and a high yield of H(2). When it was grown in 0.5% microcrystalline cellulose, approximately 82% cellulose was consumed, and the H(2) yield and maximum production rate reached 10.86 mmol/g Avicel and 2.05 mmol/L/h, respectively. Natural lignocellulosic materials without any physicochemical or biological pretreatment also supported appreciable growth of strain M18, which resulted in 56.07% to 62.71% of insoluble cellulose and hemicellulose polymer degradation in corn cob, corn stalk, and wheat straw with a yield of 3.23 to 3.48 mmol H(2)/g substrate and an average production rate of 0.10 to 0.13 mmol H(2)/L/h. CONCLUSIONS: The newly isolated strain T. thermosaccharolyticum M18 displayed effective degradation of lignocellulose and produced large amounts of hydrogen. This is the first report of a Thermoanaerobacterium species presenting cellulolytic characteristics, and this species thus represents a novel cellulolytic bacterium distinguished from all other known cellulolytic bacteria. In comparison, the extraordinary yield and specific rate of hydrogen for strain M18 obtained from lignocellulose make it more attractive in monoculture fermentation. T. thermosaccharolyticum M18 is thus a potential candidate for rapid conversion of lignocellulose to biohydrogen in a single step.